Price Competition with Reduced Consumer Switching Costs: The Case of “Wireless Number Portability” in the Cellular Phone Industry - Shi, Mengze; Chiang, Jeongwen; Rhee, Byong-Duk (Management Science, 2006)
Wireless number portability (WNP) is a telecommunication regulatory policy that requires cellular phone service providers to allow customers who switch service subscriptions to retain their original phone numbers. The right to retain the number lowers the switching cost for a consumer. Thus, the purpose of the policy is to induce more competition and facilitate the growth of new or small service providers. In this paper, we show that WNP drives market price downward as expected but with a surprising twist—rather than helping the smaller firms grow, the policy may accelerate the process of market concentration. We find that the main contributing factor to this peculiarity is the discriminatory pricing scheme prevalent in the industry—that is, a service provider charges a lower per-minute fee for the calls initiated and received within the same network than for the calls connected across two networks. Under this pricing scheme, a consumer who subscribes to a larger network would benefit more than if subscribing to a smaller network, despite the relatively higher fixed access fee that the former may charge. By lowering the barrier of switching, WNP creates a market condition conducive for a larger network to gain market share. We support our analysis with the empirical evidence gathered from Hong Kong where WNP was adopted in March 1999.